ANALISIS PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, DAN MOTIVASI, TERHADAP KINERJA KARYAWAN PT FABER CASTELL JAKARTA BARAT - Rahakbauw, Oktovina Deci; Pujaka, Gia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to determine the effect of leadership style, work discipline, and motivation on employee performance at PT Faber Castell, West Jakarta. The data used in this study are primary data obtained from questionnaires. The population was 110 respondents, using a saturated sampling method. Data collection was conducted through questionnaires distributed to 110 consumers. The results of the study showed that the t-value for leadership style was 1.989 > t-table 1.9826, with a significance level of 0.049 < 0.05, indicating that H1 was accepted. Therefore, the first hypothesis states that leadership style has a positive and significant partial effect on employee performance. The results of the study showed that the t-value for work discipline was 5.478 > t-table 1.9826, with a significance level of 0.000 < 0.05, indicating that H2 was accepted. Therefore, the second hypothesis states that work discipline has a positive and significant partial effect on employee performance. The research results show that the t-test for motivation is 6.985 < t-table 1.9826 with a significance level of 0.000 < 0.5, indicating that H3 is accepted. Therefore, the third hypothesis states that motivation has a positive and significant partial effect on employee performance variables. The F-test for all variables shows an F-test of 158.539 > F-table 2.69 and a significance level of 0.000 < 0.05. This means that the hypothesis stating that leadership style, work discipline, and motivation simultaneously have a positive and significant influence on employee performance, therefore H4 is accepted. The coefficient of determination test value of 0.813 indicates that employee performance can be explained by leadership style, work discipline, and motivation at 81.3%, while the remaining 18.7% is influenced by other factors that may have a greater influence on PT Faber Castell West Jakarta's customers.